PEMBERDAYAAN MASYARAKAT DESA BOLA KECAMATAN BOLA KABUPATEN WAJO DALAM BIDANG PENDIDIKAN, KESEHATAN DAN PEMBANGUNAN SOSIAL - Shuhufi (Pangulu Abdi: Jurnal Pengabdian Kepada Masyarakat, 2021)
The implementation of community service is a routine agenda in the Tri Dharma of Higher Education which is carried out by UIN Alauddin Makassar lecturers to the community. The implementation involves all lecturers from various faculties and departments with the assumption that the implementation of this community service in carrying out its work programs is carried out with a multi-disciplinary approach, so that community service work programs can be carried out in various approaches according to the disciplines of the lecturers who are placed at the service location.This service was carried out in Bola Village, Bola District, Wajo Regency. This service is carried out in the fields of education, health and social development. The method applied is a method of cooperation, mutual cooperation and building network relationships with village residents in Bola Village which was compiled and planned by the team through planned programs. The position of the service team is as a driving force in the midst of society that functions as academics and the community acts as practitioners of community service activities programs in responding to the problematic challenges of community life in Bola Village, Bola District, Wajo Regency.